Penerapan Model Pembelajaran Kooperatif Tipe Index Card Match untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V UPTD SD Negeri 77 Parepare - St. Maryam M; Musfirah Musfirah; Putri Syaskia Aulia Angelina (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
students. This research is a classroom action research (CAR) with a qualitative approach. The research was carried out in semester 2 of the 2022/2023 academic year with the research subjects being teachers (researchers) and 21 fifth grade students. The data analysis technique used was qualitative data analysis techniques. The focus description is in the form of learning processes and outcomes. The research instruments are observation, tests, and documentation. Based on the data obtained during the implementation, the research results in the first cycle of teacher activity were classified as sufficient (C), student activities were classified as sufficient (c), and the completeness of student learning outcomes was classified as sufficient (C), with an average value of 60; cycle II teacher activity is good (B), student activity is good (B), and student learning outcomes are good (B), with an average score of 78.33. The conclusion of the study is that by applying the index card match type cooperative learning model it can improve the process and results of learning mathematics in the subject of volume builds for class V UPTD SD Negeri 77 Parepare.